The influence of strong social ties on the choice of long-term care model for middle-aged and older adults in China - Jing, Tao; Zhao, Xinmeng; Xing, Huixia; Bao, Chuang; Zhan, Lanxi (Frontiers in Public Health, 2023)
With the acceleration of population aging in China, the care of middle-aged and older adults has become the focus of social attention. As China is an “acquaintance society,” strong social relations play an important role in residents’ access to information and resource allocation, which has an impact on the choice of long-term care models for middle-aged and older adults. Therefore, based on the 19,728 samples from the 2018 CHARLS Phase I data, an empirical analysis was conducted using a logistic dichotomous model, which showed that both kinship (p < 0.01) and friendship (p < 0.01) among social relationships positively influenced the choice of social care models for middle-aged and older adults. The analysis of the heterogeneity showed that the choice of long-term care models was significantly influenced by strong social relationships in the central and western regions and rural areas (p < 0.01). On the basis of this, the transmission mechanism of strong social relationships was further analyzed in conjunction with the further construction of the SIRS Contagion Model, which was used to describe the information transmission process. The results showed that residents who attached importance to strong social ties were more likely to incur medical transfer expenditure, thus further increasing their own demand for the formal care model. The policy implications of this study are to promote the coordinated development of long-term formal care and strong social relations, to further promote the socialization of the formal care model while relying on traditional family care, and to build a multi-level and diversified long-term care system for middle-aged and older adults.